Host Transcriptomic Response Following Administration of Rotavirus Vaccine in Infants’ Mimics Wild Type Infection - Gómez-Carballa, Alberto; Barral-Arca, Ruth; Cebey-López, Miriam; Currás-Tuala, Maria José; Pischedda, Sara; Gómez-Rial, José; Habgood-Coote, Dominic; Herberg, Jethro A.; Kaforou, Myrsini; Martinón-Torres, Federico; Salas, Antonio (Frontiers in Immunology, 2021)
Background. Rotavirus (RV) is a enteric pathogen that has devastating impact on childhood morbidity and mortality worldwide. The immunologic mechanism underlaying the protection achieved after RV vaccination is not yet fully understood. Methods. We compared the transcriptome of children affected by community-acquired RV infection, and children immunized with a live attenuated RV vaccine (RotaTeq®). Results. RV vaccination mimics the wild type infection causing similar changes in children's transcriptome, including transcripts associated with cell cycle, diarrhea, nausea, vomiting, intussusception, and abnormal morphology of midgut. A machine learning approach allowed to detect a combination of 9-transcripts that differentiates vaccinated from convalescent-naturally infected children (AUC: 0.9; 95%CI: 0.7–1), and distinguishes between acute-infected and healthy control children (in both cases, AUC: 1; 95%CI: 1–1). We identified a miRNA hsa-mir-149 that seems to play a role in the host defense against viral pathogens and may have an antiviral role. Discussion. Our findings might shed further light in the understanding of RV infection, its functional link to intussusception causes, as well as guide development of antiviral treatments and safer and more effective vaccines. The 9-transcript signature may constitute a marker of vaccine protection and helps to differentiate vaccinated from naturally infected or susceptible children.